2020
DOI: 10.1155/2020/3178642
|View full text |Cite
|
Sign up to set email alerts
|

Plasma-Derived Exosomal Circular RNA hsa_circ_0005540 as a Novel Diagnostic Biomarker for Coronary Artery Disease

Abstract: Background. Exosomes exist in almost all body fluid and contain diverse biological contents which may be reflective of disease state. Circular RNAs (circRNAs) are stable in structure and have a long half-life in exosomes without degradation, thus making them reliable biomarkers. However, the potential of exosomal circRNAs as biomarkers of coronary artery disease (CAD) remains to be established. Here, we aimed to investigate the expression levels and the potential use of exosomal circRNAs as diagnostic biomarke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 42 publications
0
25
0
Order By: Relevance
“…Has_circ_0005540 was selected from 355 circRNAs, which had a remarkably fold change and associated with CAD. (Wu et al, 2020) has_circ_0097435 ↑ Plasma HF (n=45) Healthy volunteer (n=44)…”
Section: Circrnas As Biomarkers Of Hfmentioning
confidence: 99%
See 1 more Smart Citation
“…Has_circ_0005540 was selected from 355 circRNAs, which had a remarkably fold change and associated with CAD. (Wu et al, 2020) has_circ_0097435 ↑ Plasma HF (n=45) Healthy volunteer (n=44)…”
Section: Circrnas As Biomarkers Of Hfmentioning
confidence: 99%
“…Cardiac ischemia/reperfusion (I/R) could increase the secretion of EVs; the following RNA-seq of EVs identified 185 significantly differentially expressed circRNAs, 119 downregulated and 66 upregulated, compared with the sham, suggesting that circRNAs in cardiac EVs might indicate development of I/R as biomarkers (Ge et al, 2019). Using circRNAs to improve the discriminatory power for CVD has been discussed (Wu et al, 2020). Exosmal circRNA expression levels in exosomes was analyzed from 3 plasma samples of CAD patients and 3 paired controls using RNA sequencing.…”
Section: Circrnas As Biomarkers Of Hfmentioning
confidence: 99%
“…It was speculated that exosome lncRNA HIF1A-AS1 could be used as a potential biomarker of AS (Wang et al, 2017). Another study analyzed circRNA expression in plasma exosomes from patients with CAD and controls using RNA sequencing and found that plasma exosomal hsa_circ_0005540 could be a promising biomarker for the diagnosis of CAD (Wu et al, 2020).…”
Section: Exosomal Non-coding Rnas In Coronary Artery Disease Diagnosismentioning
confidence: 99%
“…In fact, augmented circSMARCA5 levels are associated with a decreased segment stenosis score as well as with decreased cardiovascular risk [58]. Furthermore, RNA sequencing from plasma exosomes of CAD and non-CAD patients identified 335 exosomal circRNAs to be differentially expressed among the two groups [59]. After adjusting for risk factors, circ0005540 was upregulated in CAD patients, and displayed high sensitivity and specificity for identifying CAD patients, suggesting its potential as a CAD biomarker [59].…”
Section: Coronary Artery Diseasementioning
confidence: 99%